LEARNING METHOD WHILE PLAYING DALAM MENINGKATKAN VERBAL SMART ANAK - Fathor Rozi; Siti Muti’atul Habibah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2023)
This study aims to find out how the application of the learning method while playing or also called the learning method while playing in improving verbal smart language and speaking skills in early childhood. This study uses a qualitative approach with a case study type. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques are carried out systematically starting with data display, condensation, and drawing conclusions. The results of the field research found that the learning process in which the learning while playing method was applied through role playing, playing flash cards, and singing while playing, was able to improve verbal smart children's language and speaking abilities. because the child will easily absorb, remember and get new vocabulary from the surrounding environment. The implication is that there is a need for an approach used by teachers using other game methods that are able to stimulate the development of language and speech in early childhood to optimize children's verbal smarts.